Disaster resilience and asset prices - Pagano, Marco; Wagner, Christian; Zechner, Josef (Journal of Financial Economics, 2023)
Using the COVID-19 pandemic as a laboratory, we show that asset markets assign a time-varying price to firms’ disaster risk exposure. The cross-section of stock returns reflected firms’ different exposure to the pandemic, as measured by their vulnerability to social distancing. As predicted by theory, realized and expected return differentials moved in opposite directions, initially widening and then narrowing. When inferred from market outcomes, firm resilience correlates mainly with exposure to social distancing: vulnerability to social distancing is priced in changes of firms’ expected returns, while measures of financial and environmental resilience are not.